Midterm failure of combined phacoemulsification with trabecular microbypass stenting: Clinicopathological analysis. Issue 5 (May 2018) - Shah, Manjool; Campos‐Möller, Xavier; Werner, Liliana; Mamalis, Nick; Ahmed, Iqbal Ike K.
Abstract : N/A: A propagation of microinvasive glaucoma surgery (MIGS) techniques and devices has resulted in the availability of multiple new modalities for surgical intervention for open‐angle glaucoma. As MIGS devices and methods approach a new phase in maturity, midterm failures will inevitably be reported. Although MIGS techniques prioritize safety, an understanding of the potential mechanisms of failure is paramount. In this case of a midterm failure of a trabecular microbypass, clinical findings and pathological correlates allow for a comprehensive understanding of the means by which MIGS devices might fail and offer the opportunity for intervention and potential prevention.